New Cutting Edge Intermediate Teachers Book and Test Master CD-Rom Pack - Helen Barker (Harlow Pearson Education Limited, 2006)
New Cutting Edge Intermediate Teacher's Resource Book gives teachers everything they need to use the course successfully in a variety of teaching situations: Step-by-step teacher's notes Teacher's tips section with practical ideas on teaching vocabulary and grammar, using the Mini-dictionary and making speaking tasks work Photocopiable Resource Bank includes learner-training worksheets, communication activities and progress tests Includes the Test-Master CD-ROM for easy customised tests: Placement, Module, Mid-Course, and End of Level Tests The audio files for the listening tests are conveniently located on the same CD
Keywords: Language; English Language